First-Principles Investigation on Electrochemical Performance of Na-Doped LiNi1/3Co1/3Mn1/3O2 - Gao, Yumei; Shen, Kaixiang; Liu, Ping; Liu, Liming; Chi, Feng; Hou, Xianhua; Yang, Wenxin (Frontiers in Physics, 2021)
The cathode material LiNi1/3Co1/3Mn1/3O2 for lithium-ion battery has better electrochemical property than LiCoO2. In order to improve its electrochemical performance, Na-doped LiNi1/3Co1/3Mn1/3O2 is one of the effective modifications. In this paper, based on the density functional theory of the first-principle, the conductivity and the transition state of the Na-doped LiNi1/3Co1/3Mn1/3O2 are calculated with Materials studio and Nanodcal respectively. The calculation results of the band gap, partial density of states, formation energy of intercalation of Li+, electron density difference and potential energy of electrons show that the new cathode material Li1-xNax Ni1/3Co1/3Mn1/3O2, when the doped amount is x=0.05~0.06 mol, has the better conductivity. The whole 3D potential map of the new material can be gotten in nanodcal, which demonstrates Na doping can reduce the potential well and increase the removal rate of lithium ion. The theoretical calculation results match well with the experiment ones. Our method and analysis can provide some theoretical proposals for the electrochemical performance study of the doping. This method used in the first-principle can be also applied into the performance study of the new optoelectronic devices.